A porcine circovirus type 2d-based virus-like particle vaccine induces humoral and cellular immune responses and effectively protects pigs against PCV2d challenge - Kim, Kiju; Choi, Kyusung; Shin, Minna; Hahn, Tae-Wook (Frontiers in Microbiology, 2024)
The pathogenic porcine circovirus type 2 (PCV2) leads to significant economic losses in pig production. PCV2d is currently the dominant genotype causing porcine circovirus-associated disease (PCVAD) worldwide. Therefore, development of a recombinant PCV2d-based vaccine is required to elicit complete protection against PCV2d infection. In this study, we generated virus-like particles of PCV2d-based capsid protein (Bac-2dCP) using a baculovirus expression system and evaluated its protective efficacy against PCV2d infection in specific pathogen-free (SPF) pigs. Three-week-old SPF miniature pigs were intramuscularly immunized with purified Bac-2dCP and intranasally challenged with PCV2d at 4 weeks post-vaccination. The Bac-2dCP group showed significantly higher IgG levels and neutralizing antibodies against PCV2b and PCV2d genotypes, as well as increased interferon- levels, and increased body weight and average daily weight gain compared with positive (challenged) and negative (unchallenged) controls. In particular, the Bac-2dCP group showed almost complete absence of PCV2d DNA in serum, nasal, and rectal swabs and in lung, lymph node, and kidney tissue samples. However, the positive control group exhibited low levels of neutralizing antibody, and high levels of PCV2 DNA in serum, swab, and tissue samples, resulting in PCV2-associated pathological lesions. The results of this study demonstrated that a recombinant Bac-2dCP vaccine conferred complete protection against a PCV2d challenge in SPF miniature pigs.